Early administration of lopinavir/ritonavir plus hydroxychloroquine does not alter the clinical course of SARS‐CoV‐2 infection: A retrospective cohort study. Issue 3 (28th September 2020) - Giacomelli, Andrea; Pagani, Gabriele; Ridolfo, Anna L.; Oreni, Letizia; Conti, Federico; Pezzati, Laura; Bradanini, Lucia; Casalini, Giacomo; Bassoli, Cinzia; Morena, Valentina; Passerini, Simone; Rizzardini, Giuliano; et al.
Abstract: As it has been shown that lopinavir (LPV) and hydroxychloroquine (HCQ) have in vitro activity against coronaviruses, they were used to treat COVID‐19 during the first wave of the epidemic in Lombardy, Italy. To compare the rate of clinical improvement between those who started LPV/ritonavir (LPV/r)+HCQ within 5 days of symptom onset (early treatment, ET) and those who started later (delayed treatment, DT). This was a retrospective intent‐to‐treat analysis of the hospitalized patients who started LPV/r + HCQ between 21 February and 20 March 2020. The association between the timing of treatment and the probability of 30‐day mortality was assessed using univariable and multivariable logistic models. The study involved 172 patients: 43 (25%) in the ET and 129 (75%) in the DT group. The rate of clinical improvement increased over time to 73.3% on day 30, without any significant difference between the two groups (Gray's test P = .213). After adjusting for potentially relevant clinical variables, there was no significant association between the timing of the start of treatment and the probability of 30‐day mortality (adjusted odds ratio [aOR] ET vs DT = 1.45, 95% confidence interval 0.50‐4.19). Eight percent of the patients discontinued the treatment becausebecause of severe gastrointestinal disorders attributable to LPV/r. The timing of the start of LPV/r + HCQ treatment does not seem to affect the clinical course of hospitalized patients with COVID‐19. Together with the severe adverse events attributable to LPV/r, this raises concerns about the benefit of using this combination to treat COVID‐19. Highlights: Lopinavir/ritonavir (LPV/r) plus hydroxychloroquine (HCQ) have been repurposed to treat COVID‐19. We studied the combination of LPV/r plus HCQ in 172 hospitalised patients with COVID‐19. Early LPV/r plus HCQ treatment was not associated with a faster improvement in the patients clinical condition. Early LPV/r plus HCQ treatment did not reduce 30‐day mortality. Eight percent of the patients discontinued the treatment due to severe adverse events.